Efficacy of corrosion control and pipe replacement in reducing citywide lead exposure during the Flint, MI water system recovery. Issue 11 (25th August 2020) - Roy, Siddhartha; Edwards, Marc A.
Abstract : Enhanced corrosion control and replacement of all lead-based pipes are expected to reduce citywide lead exposure by about 72–84%. However, Flint's post-lead pipe era will not result in completely lead free drinking water. Abstract : Flint biosolids monitoring data demonstrate a sustained decline in total lead release to potable water from plumbing since the 2014–2015 Flint Water Crisis (FWC), due to enhanced corrosion control treatment (3 mg L −1 orthophosphate as PO4 ) and removing of ∼80% of lead and galvanized iron service lines through early 2020. The official 90th percentile water lead levels, which have now met the federal Lead and Copper Rule threshold of 15 μg L −1 for the last four years, are in agreement with those predicted by a previously established biosolids regression model. There is also no longer a correlation between the percentage of children under 6 years of age with blood lead ≥ 5 μg dL −1 and biosolids lead mass in the 44 months post-FWC (Nov 2015–Jun 2019), nor are there continued correlations between plumbing-related metals in the biosolids, with the exception of Cu:Zn found in brass alloys that remain installed in homes. After Flint achieves 100% replacement of lead and galvanized service line pipes, a biosolids data analysis predicts that the remaining sources of waterborne lead including leaded brass, lead solder and legacy lead in pipe scale, will still release about 16–28% of the pre-FWC lead mass to potable water. The efficacy of enhanced corrosion control and replacement of service lines that contain lead is, therefore, on the order of 72–84% effective at reducing citywide lead exposure, yet some significant water lead sources will still remain even after pipe replacement is complete.